Pemberdayaan Pengurus Masjid Dalam Me-Manage Jamaah Pada Masjid Al-Irsyad Ujung Baru Kota Parepare - Erza Widya Ningsih Erza Widya Ningsih; Darmawati; Ramli (Jurnal Kajian Manajemen Dakwah, 2021)
This study discusses the empowerment of mosque administrators in managing congregations. The purpose of the study was to find out how to empower mosque administrators in managing congregations and to find out supporting factors and inhibiting factors in managing congregations. by conducting previous observations and collecting data as well as interviews and documentation. The results of this study indicate that: 1) Empowerment of the management of the Al-Irsyad mosque exists and has a portion according to the rules of the ministry of religion while the empowerment of mosque administrators is not based on physical building but also non-physical which means how mosque administrators can prosper the mosque and build facilities needed by the congregation as well as to build the mindset of the congregation so that they can become better. 2) Supporting factors in managing congregations are the existence of funds, zakat, adequate facilities, a lot of assistance from the community, and the harmony of the management and congregation, and the strategic location of the mosque, there are also inhibiting factors for the congregation who are still less focused and management management is still lacking. communication.